2009
DOI: 10.1146/annurev-nutr-080508-141205
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Significance of Lipid Rafts

Abstract: The structure, size, stability, and functionality of lipid rafts are still in debate, but recent techniques allowing direct visualization have characterized them in a wide range of cell types. Lipid rafts are potentially modifiable by diet, particularly (but not exclusively) by dietary fatty acids. However, it is not clear whether dietary polyunsaturated fatty acids (PUFAs) are incorporated into raft lipids or whether their low affinity to cholesterol disallows this and causes phase separation from rafts and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 176 publications
(181 reference statements)
2
66
0
1
Order By: Relevance
“…[23,24] Furthermore, incorporation of ω-3 PUFAs into cell phospholipid membranes changes the fluidity, structure and function of lipid rafts, resulting in altered downstream signaling by cell surface receptors, such as epidermal growth factor receptor. [25,26] Moreover, ω-3 PUFAs are highly peroxidizable and increase levels of intracellular reactive oxygen species (ROS), a byproduct of cell growth. Although moderately increased levels of ROS damage DNA and promote mutagenesis in cells, recent evidence indicates that high ROS levels exert an oxidative stress that can restrain tumor progression and metastasis by causing cell senescence or death.…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] Furthermore, incorporation of ω-3 PUFAs into cell phospholipid membranes changes the fluidity, structure and function of lipid rafts, resulting in altered downstream signaling by cell surface receptors, such as epidermal growth factor receptor. [25,26] Moreover, ω-3 PUFAs are highly peroxidizable and increase levels of intracellular reactive oxygen species (ROS), a byproduct of cell growth. Although moderately increased levels of ROS damage DNA and promote mutagenesis in cells, recent evidence indicates that high ROS levels exert an oxidative stress that can restrain tumor progression and metastasis by causing cell senescence or death.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma membrane microdomains are likely to be of diverse nature, exhibiting altering substable L o states (9,(47)(48)(49)(50)(51)(52). Therefore, the DRM/DSF protein abundance ratios can better reflect global changes in protein-sterol interactions and account for total protein abundance changes compared with studying abundance changes in DRM only.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not defined yet if targeting lipid rafts in vivo might impair physiological functions. For instance, it is not clear whether dietary LC-PUFA are incorporated into raft lipids or whether their low affinity to cholesterol disallows this and causes phase separation from rafts and displacement of raft proteins [128]. Moreover, it was shown that depletion of cholesterol leads to instability of surface AMPA-glutamate in lipid rafts, which was accompanied by gradual loss of synapses and dendritic spines [129].…”
Section: Discussionmentioning
confidence: 99%